Innovations and development of Covid-19 vaccines: A patent review. Issue 1 (January 2022) - Alshrari, Ahmed S.; Hudu, Shuaibu A.; Imran, Mohd; Asdaq, Syed Mohammed Basheeruddin; Ali, Alreshidi M.; Rabbani, Syed Imam
Abstract: More than 125 million confirmed cases of COVID-19 have been reported globally with rising cases in all countries since the first case was reported. A vaccine is the best measure for the effective prevention and control of COVID-19. There are more than 292 COVID-19 candidates' vaccines being developed as of July 2021 of which 184 are in human preclinical trials. A patent provides protection and a marketing monopoly to the inventor of an invention for a specified period. Therefore, vaccine developers, including Moderna, BioNTech, Janssen, Inovio, and Gamaleya also filed patent applications for the protection of their vaccines. This review aims to provide an insight into the patent literature of COVID-19 vaccines. The patent search was done using Patentscope and Espacenet databases. The results have revealed that most of the key players have patented their inventive COVID-19 vaccine. Many patent applications related to COVID-19 vaccines developed via different technologies (DNA, RNA, virus, bacteria, and protein subunit) have also been filed. The publication of a normal patent application takes place after 18 months of its filing. Therefore, many patents/patent applications related to the COVID-19 vaccine developed through different technology may come into the public domain in the coming days.